2019
DOI: 10.24875/ric.18002617
|View full text |Cite
|
Sign up to set email alerts
|

Role of Genetic Susceptibility in Nicotine Addiction and Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality in developed countries. Although cigarette smoking is the major risk factor, only 10-20% of smokers develop COPD. The extent of cigarette smoking (pack-years and smoking duration) accounts for only 15% of the variation in lung function, indicating that differences in susceptibility to COPD must exist. We provide an overview of the complexity of nicotine addiction and COPD, with special attention to the involvement of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 187 publications
0
15
0
1
Order By: Relevance
“…Also, multiple studies have evaluated the participation of genetics factors in the COPD pathogenesis, 30 including PiS and PiZ variants, mostly applying this phenotypebased concept and leaving out the variability for each polymorphism and the potential contribution to COPD and/or its clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…Also, multiple studies have evaluated the participation of genetics factors in the COPD pathogenesis, 30 including PiS and PiZ variants, mostly applying this phenotypebased concept and leaving out the variability for each polymorphism and the potential contribution to COPD and/or its clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is classified as a multifactorial disease, which means that in addition to the environmental factors strongly associated with the physiopathology of the disease, genetic factors, mostly single nucleotide polymorphisms (SNPs), have also been determined to contribute to the susceptibility and clinical variables of COPD [ 6 ]. In 2009, through genome-wide association studies (GWAS), several SNPs in the HHIP (hedgehog-interacting protein) gene were identified [ 7 ]; however, in this initial study, the results did not reach strict levels of significance.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular factors associated with a genetic predisposition to COPD have been widely studied (Pérez-Rubio et al, 2019). Several GWASs have identified a genetic loci of susceptibility, including FAM13A, CHRNA5/3, IREB2, MMP3/MMP12, TGFB2, and HHIP.…”
Section: Discussionmentioning
confidence: 99%